Evaluating the Stability of Type II Genial Tubercle Fracture Repair: A Case Report. Issue 3 (September 2022) - Goodenough, Mark; Gersten, Joshua; Izzo, Steven; Yusupov, Yuriy
This case explores the management of a type II genial tubercle fracture (GTF) repair and its stability. Few reports describing the surgical correction of this fracture type exist and among the available literature detailing GTF repair, most do not include post-surgical clinical follow-up. The case herein follows the treatment of a 35-year-old male sustaining poly mandibular trauma. Plate fixation, trans-osseous wiring and maxillomandibular fixation (MMF) were used to secure the genial tubercle to a stable mandibular complex. A 6-week closed reduction protocol was implemented for management of a concomitant subcondylar fracture. Although the patient displayed improvements clinically, genial tubercle (GT) displacement was seen radiographically at the completion of treatment. This paper aims to reassess the durability of trans-osseous wiring as a sole means of fracture reduction. Additional studies documenting follow-up evaluations are needed to verify treatment outcomes of this rare fracture pattern.